A loss-recovery evaluation tool for debris flow. (July 2019) - Gan, Lu; Wang, Yuanyuan; Lin, Zhiyi; Lev, Benjamin
Abstract: In recent years, various severely natural disasters have swept the world, especially the debris flow in geological disaster, which causes huge losses and needs lengthy recovery. This motivates a comprehensive consideration on post-disaster loss and recovery in a closed loop point of view, based on a novel systematic two-stage evaluation method, this study focuses on loss evaluation and emergency resilience decision of debris flow. In the first stage, the weighing technique is applied to a reasonably established index system for loss evaluation. Then, Combined with technique for order preference by similarity to Ideal solution (TOPSIS) and the grey relation analysis (GRA) is utilized to evaluate the loss level of debris flow. In the second stage, an improved restoration triangle model is used to evaluate the post-disaster reconstruction and recovery. In order to solve the complex computational problems, a specific software system was developed to ensure convenience and efficiency in practical applications. The validity of the whole study is verified by case study. The results demonstrate that the proposed method can help decision makers generate strategies in risk management. Graphical abstract: The framework of the post-disaster evaluation of debris flow can be summarized as in Fig. 1with following three research phases. Phase I: To establish a loss evaluation index system and evaluate the loss of post-disaster by using a comprehensive GRA- TOPSIS methodPhase II: To obtain the resilience of disaster areas and provide better guideline for DMs by using a novel resilience triangle modelPhase III: To calculate the result and achieve visualization by designing a software system.Image 1 Highlights: Established an integrated closed loop model for post-disaster loss and resilience evaluation. Designed a software system to provide users with friendly and visual implementation. Building Information Modeling (BIM) is utilized in debris flow loss assessment and reconstruction.